THE EFFECT OF COORDINATION AND LEADERSHIP STYLE ON IMPROVING THE PERFORMANCE OF THE SIPODECENG VILLAGE GOVERNMENT APPARATUS - Naming Pallajareng; Abdul Jabbar; Sandi Lubis; Mutiah Khaerunnisa (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2026)
This study analyzes the influence of coordination and transformational leadership on village apparatus performance in Sipodeceng Village, Sidenreng Rappang Regency. Using a survey of 12 village officials with simple linear regression analysis, results show that coordination (p=0.424) and transformational leadership (p=0.154) have no significant effect on apparatus performance. These findings indicate that modern management concepts are not always applicable in small-scale village government organizations with simple hierarchical structures and traditional work cultures. Apparatus performance is more influenced by other factors such as individual competence, intrinsic motivation, and supporting facility availability. This study provides important empirical evidence on the need for contextualization of management theory in local organizational environments with unique characteristics, and practical implications for developing village apparatus training programs that are more contextually appropriate.